2004
DOI: 10.1007/bf03033443
|View full text |Cite
|
Sign up to set email alerts
|

Studies on homocysteine and dehydroepiandrosterone sulphate plasma levels in alzheimer’s disease patients and in Parkinson’s disease patients

Abstract: Homocysteine (HC) and dehydroepiandrosterone sulphate (DHEAS) plasma levels have been evaluated in groups of male and female patients with Parkinson's disease (PD) and in a group of female patients with Alzheimer's disease (AD) and compared with the corresponding plasma levels observed in a group of age-matched subjects. It has been confirmed that HC plasma levels are enhanced in both PD and AD patients. As far as the DHEAS plasma levels are concerned no changes have been observed in PD patients while a marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
(32 reference statements)
3
19
0
Order By: Relevance
“…Such a view has great clinical relevance and may be a new target for therapeutic intervention in AD. In fact, it should be mentioned that high plasma levels of Hcy have been demonstrated as a risk factor for Alzheimer's disease [56] and Hcy plasma levels steadily increase with age reaching high values in Alzheimer and Parkinson patients [57]. Thus, our own findings and data in the literature support the hypothesis that Hcy by interacting with A causes a conformational change in the monomer favouring the -sheet conformation.…”
Section: Discussionsupporting
confidence: 82%
“…Such a view has great clinical relevance and may be a new target for therapeutic intervention in AD. In fact, it should be mentioned that high plasma levels of Hcy have been demonstrated as a risk factor for Alzheimer's disease [56] and Hcy plasma levels steadily increase with age reaching high values in Alzheimer and Parkinson patients [57]. Thus, our own findings and data in the literature support the hypothesis that Hcy by interacting with A causes a conformational change in the monomer favouring the -sheet conformation.…”
Section: Discussionsupporting
confidence: 82%
“…The proteins most probably induce oxydative stress [15,16]. As indicated in reports on the subject [17], also elevated levels of homocysteine (Hcy), in degenerative diseases, might be responsible for increased oxydative stress. It has been also suggested that the pro-oxidative activity of Hcy in AD most probably involves direct interaction of Hcy with NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations have shown that elevated Hcy plasma levels has been identified in patients with neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD) and multiple sclerosis (MS) (Clarke et al, 1998;Kuhn et al, 1998;Genedani et al, 2004;Agnati et al, 2005;Russo et al, 2008), and that there was a tight correlation between the elevated Hcy plasma levels and cognitive impairment in the elderly, AD patients and MS patients by the retrospective and prospective studies (Prins et al, 2002;Seshadri et al, 2002;Russo et al, 2008). Elevated Hcy plasma levels have been recognized as an important risk factor for cognitive dysfunction (Miller, 2003).…”
Section: Introductionmentioning
confidence: 99%